A SIMS study of cation and anion diffusion in tantalum oxide. Issue 2 (13th December 2017) - Gries, U. N.; Schraknepper, H.; Skaja, K.; Gunkel, F.; Hoffmann-Eifert, S.; Waser, R.; De Souza, R. A.
Abstract : Diffusion experiments reveal that anions are more mobile than cations in L-Ta2 O5 ; together with literature data, they suggest that oxygen interstitials are the defects responsible for anion diffusion. Abstract : Ion transport in ceramics of the low-temperature phase of tantalum pentoxide, L-Ta2 O5, was examined by means of diffusion experiments and subsequent analysis of diffusion profiles with time-of-flight secondary ion mass spectrometry (ToF-SIMS). 18 O/ 16 O isotope anneals were used to investigate oxygen diffusion, and oxygen tracer diffusion coefficients were obtained for the temperature range of 623 ≤ T /K ≤ 873 at an oxygen partial pressure of p O2 = 0.2 bar and for the oxygen partial pressure range of 10 −2 ≤ p O2 /bar ≤ 10 0 at a temperature of T = 723 K. Cation diffusion in Ta2 O5 was probed by using chemically similar niobium as the diffusant (in the absence of stable tantalum isotopes). Thin films of Nb2 O5 were deposited onto Ta2 O5 ceramics; diffusion anneals yielded niobium diffusion coefficients for the temperature range of 1073 ≤ T /K ≤ 1223 at an oxygen partial pressure of p O2 = 0.2 bar. Comparison of the measured diffusion coefficients strongly suggests that oxygen is many orders of magnitude more mobile than niobium in L-Ta2 O5 at these temperatures and at p O2 = 0.2 bar. The electrical conductivity was also determined in the range 950 ≤ T /K ≤ 1200 and 10 −23 ≤ p O2 /bar ≤ 10 −2 . Considered together with the measured diffusion coefficients, the conductivity data indicate that under oxidising conditions conduction is due to oxygen ions above T = 1090–1130 K and due to electron holes below this temperature range. Point-defect models are presented that are consistent with these transport data and with conductivity data in the literature. They suggest that under oxidising conditions oxygen interstitials are the majority ionic charge carriers in L-Ta2 O5 . The implications for resistive switching devices are discussed.